PENGARUH MEDIA BIG BOOK TERHADAP HASIL BELAJAR IPS SISWA DI SDN 1 PARE-PARE KOTA PARE-PARE - Fajrin, Syarifah Nur; Ashar, Ashar (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2019)
This type of research is quantitative research. The research used is Experimental Research. The research design used was One Group Pretest-Posttest Design. The sampling technique in this study is the purposive sampling technique, based on certain criteria, namely the low learning outcomes. The sample of this research is the fourth grade students of SDN 1 Pare-pare with a total of 28 students and the data collection techniques of this study are the test and observation techniques. The procedure of this research was carried out in accordance with the Experiment procedure which was to provide pretest, give treatment and posttest. The hypothesis of this study is Ho: µ1 = µ2 or Ha: µ1 ? µ2 with the explanation that Ho = There is no influence of the Big Book Media on Social Studies learning outcomes of fourth grade students at SDN 1 Pare-pare Pare-pare City and Ha = There is the influence of Big Big media Book on social studies learning outcomes of fourth grade students at SDN 1 Pare-pare, Pare-pare City. The expected results in this study are that there is the influence of Big Book media on the learning outcomes of Social Studies students SDN 1 Parepare. This is proven based on the results of the research hypothesis test that is a significance value of 0,000 <0.005 so that Ho is rejected and Ha is accepted. Big Book Media is also one of the learning media that can be used to improve students' social studies learning outcomes.